Analisis Kesalahan Berbahasa Tataran Fonologi Dalam Surat Kabar Jawa Pos Tahun 2024 - Miftahul Huda; Elena Jesica (Pendidikan Bahasa dan Sastra Indonesia, 2024)
Language errors are deviations from linguistic rules that do not comply with language guidelines in the pronunciation or writing of phrases, words, sentences or paragraphs. This research aims to describe language errors in the April 5 2024 edition of the Java Post newspaper at the phonological level. This research uses a descriptive qualitative method that discusses data by describing it with words. Data collection techniques in this research used listening techniques and note-taking techniques. Based on the results of the analysis of the Jawa Pos newspaper in the table above, 11 data on phonological level language errors have been found in the Jawa Pos newspaper. These errors include one error in the use of capital letters, one error in writing prefixes, one error in prepositions, one error in clitics, one error in particles, three errors in rewriting words, and three errors in abbreviations.